NIRS Training 2019 | Interview with Bolaji Oluwatomilola | IITA, Ibadan - June 24-July 5 2019 - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2020)
Bolaji recounts her experience after two weeks of intense training with state-of-the-art equipment at the International Institute of Tropical Agriculture (IITA), Ibadan.